Intervenção para crianças, adolescentes e suas cuidadoras expostas à VPI - Otaguiri, Alliny Tiemi Moia (Universidade Federal de São Carlos, 2019)
Intimate partner violence (IPV) consists in a public health matter, which affects not only its direct victims, but also thousands of children who live in homes where the phenomenon occurs. It is known that the exposure of children and adolescents to IVP may lead to short-, medium-, and long-term impacts throughout their development. Thus, intervention programs aimed at this population are necessary, both from the attenuation of IPV exposure consequences, as well as from the prevention of the perpetuation of the cycle of violence point of view. Also, it should be noted that both the quality of the relationship between the mother or caretaker and the child, as well as the mental health situation of the mother/caregiver carry deep influence along the development of children. Considering such context, the present dissertation was developed, and composed of three scientific articles related to the theme. The first article consisted of a literature review which aimed to identify interventions conducted with parallel groups of mothers and their children who have been exposed to IPV. The analyses of the 13 selected articles has allowed us to conclude that intervention programs which treat both mothers and children lead to positive results for both parts. Also, improvements on mothers’ symptoms were related to improvements on their children’s. In this way, intervention programs that aim at the prevention and treatment of the effects of IPV exposure, both for mothers/caregivers and for their children, present as important resources. The second article describes the process of adapting the Community Treatment Program of Witness Groups of Women Abuse (CGTP), a Canadian intervention program for children, adolescents and their mothers/caregivers exposed to IPV, to the Brazilian reality. Our research began once the authorization to conduct the adaptation process was granted by the owners of the original program. The translated version of the program was submitted to the evaluation of expert judges, who provided their assessments of the content and relevance of the activities to the Brazilian reality, in terms of cultural, semantic and conceptual adequacy. The judges found the structure, approach and activities of the program to be relevant to the Brazilian context. The modification of some games and activities included in the sessions was suggested, as well as the refinement of some language aspects, such as the use of a more informal language on the materials intended for participants. Finally, on the third study, professionals with experience on working with the targeted population (children, adolescents and their mothers/caregivers exposed to IPV) were interviewed. This study was developed in addition to the cross-cultural adaptation procedure, and the participants were consulted about what they considered relevant for the development of an intervention such as the CGTP. The professionals pointed out characteristics such as: conducting sessions in groups divided by age, with occasional meetings between families and children and ludic activities. They recommended the approach of themes such as self-protection, assertive communication skills, feelings of guilt and shame, prevention of violence, rules, limits, notions of bodily autonomy and consent, emotional education, self-esteem, among others. By the end of the adaptation process, it was possible to conclude that the adapted intervention program (“Vida livre de violência para mães e filhos”) was adequate to Brazilian reality.
Intervention for children, adolescents and their caregivers exposed to IPV
Keywords: Violência entre parceiros íntimos; Crianças; Exposição à violência; Intervenção; Programa de intervenção; Intimate partner violence; Children; Exposure to violence; Intervention; Intervention program; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA